2021
DOI: 10.31699/ijcpe.2021.4.1
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Ni-WO3/Sulfated Zirconia Nano catalyst for Isomerization of N-Hexane and Iraqi Light Naphtha

Abstract: This work deals with preparation of Sulfated Zirconia catalyst (SZ) for isomerization of n-hexane model and refinery light naphtha, as well as enhanced the role of promoters to get the target with the mild condition, stability, and to prevent formation of coke precursors on strong acidic sites of the catalyst. The prepared SZ catalysts were characterization by fourier transform infrared spectroscopy (FTIR), X-ray diffraction (XRD), Brunauer –Emmett-Teller (BET) surface area analysis, Thermogravimetric Analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 16 publications
1
5
0
Order By: Relevance
“…The results also showed that the maximum isomer's selectivity and yield were obtained at the temperature 250 °C and LHSV =2.46 ℎ𝐼𝐼 −1 , which was 86% and 76%, respectively. This result agrees with other research published in the public domain [16,26,27].…”
Section: Effect Of Changing Lhsv and Temperature On Selectivity And Y...supporting
confidence: 94%
See 1 more Smart Citation
“…The results also showed that the maximum isomer's selectivity and yield were obtained at the temperature 250 °C and LHSV =2.46 ℎ𝐼𝐼 −1 , which was 86% and 76%, respectively. This result agrees with other research published in the public domain [16,26,27].…”
Section: Effect Of Changing Lhsv and Temperature On Selectivity And Y...supporting
confidence: 94%
“…Naphtha with a higheroctane number was produced when the temperature was above 270 °C; however, the rate of isomer production slowed, and the process shifted towards hydrocracking above this point. Kamel et al [16] analyzed the isomerization of n-hexane and LN on a catalyst of a Ni-WO3/Sulfated Zirconia catalyst at temperatures between 130 and 250 °C, LHSV = 1 hr 1 and constant pressure, i.e., 6 bar. At an operating temperature of 150 ℃, the highest selectivity and conversion for n-hexane isomerization using Ni-WSZ were 96% and 80.1%, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…1 shows a schematic of the Penex™ isomerization unit. The initial mathematical model step characterization of the subject is to build scheme reactions for hydrocarbon during the isomerization process [15]. The mathematical model assumptions were considered as the following [39][40][41][42][43]:…”
Section: Mechanism Of the Isomerization Process For Light Naphtha (C5...mentioning
confidence: 99%
“…Within the past ten years, few studies have been conducted on kinetic models for the isomerization of n-alkanes [12][13][14][15][16][17][18][19][20][21]. The type of feedstock and operating conditions of the most significant studies are reported in Table 1.…”
Section: Introductionmentioning
confidence: 99%
“…Nanomaterials have gained importance in developing new and different industrial applications due to their unique shape, size, and high surface area to volume ratio [1,2,3]. Iron oxide nanoparticles (FeO NPs) are usually interested in modern nanotechnology because of their superior magnetic properties, and their high magnetic susceptibility, and their distinctive properties where they have a high ability to inhibit the growth of microorganisms [4,5].…”
Section: Introductionmentioning
confidence: 99%